Significant shortcomings in vape product labelling - Look, Keyun; Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Long, Chiau Ming * (Star Media Group Berhad, 2023)
The current lack of adequate labelling on vape liquids, also known as e-liquid or e-juice, has contributed to an increase in acute nicotine poisoning among children.